The effects of indigenous South African plant extracts (cotyledon c. orbiculata and tulbaghia. violacea) on triple negative breast cancer cells - Alaouna, Mohammed (University of the Witwatersrand, Johannesburg, 2024)
This dissertation explored the potential therapeutic applications of water and methanol extracts of C. orbiculata and Tulbaghia violacea, indigenous to Southern Africa, targeting triple-negative breast cancer (TNBC). TNBC, a significant subset of breast cancer cases, is notably challenging because of the absence of key hormone receptors, often leading to less favourable patient outcomes and a high relapse rate within five years. The research approach was both thorough and meticulous, utilising two cell lines: one representing normal breast tissue and the other representing TNBC. Extensive cytotoxicity assays were conducted to determine the IC50 values for TNBC cells, which is critical for understanding how plant extracts affect cellular activities such as migration, invasion, adhesion, cell cycle regulation, and apoptosis induction. Additionally, the antioxidant properties of these extracts were examined, which showed significant effects, especially in the aqueous extract of Tulbaghia violacea, on TNBC cellular dynamics. This study employed a comprehensive array of analytical techniques, including Fourier transform infrared spectroscopy (FTIR), gas chromatography-mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR) spectroscopy, to identify the specific molecular constituents of these extracts. Computational docking studies have focused on the interactions between these molecules and the anti-apoptotic protein, COX2. Whole transcriptome sequencing of RNA from both TNBC and normal breast cells treated with T. violacea extract provided valuable insights into the affected signaling pathways. An antibody array assay further elucidated protein changes in the receptor tyrosine kinase (RTK) pathway. The half-maximal inhibitory concentration (IC50) values were determined for the aqueous and methanol extracts of T. violacea at 400 μg/mL and 820 μg/mL, respectively, and for C. orbiculata at 830 μg/mL and 700 μg/mL, respectively. Exposure to the water-soluble extract of T. violacea resulted in a marked increase in apoptosis in TNBC cells, with approximately 82% undergoing programmed cell death, compared to 32% in normal breast cells. Chemical profiling identified a range of compounds, including 36 distinct compounds identified through GC-MS and 61 identified through NMR, many of which bear structural similarities to known anti-cancer agents. Notably, five compounds demonstrated a high affinity forbinding to COX2, with d-glycero-d-galacto-heptose achieving an impressive docking score, surpassing several established COX2 inhibitors. This study highlights the therapeutic potential of T. violacea compounds and lays the groundwork for further exploration of their mechanisms of action and potential applications in cancer treatment. This emphasises the importance of investigating natural plant extracts as a source for the development of new and effective treatments for TNBC, which is an area of urgent need in oncology
A dissertation submitted in fulfillment of the requirements for the degree of Doctor of Philosophy (Internal Medicine) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: TNBC; Biomarkers; Genetic mutations; Phytochemicals; Gonadotropin-releasing hormone Wnt pathway; ErbB receptors; GC-MS analysis; Plant compounds; UCTD; Signaling pathways; SDG-3: Good health and well-being